Upregulation of stomatin is associated with poor prognosis and promotes tumor progression of orbital diffuse large B-cell lymphoma - Chen, Wen; Chi, Jingyi; Song, Weichen; Li, Xiuyun; Ma, Jinlei; Liu, Xinyu; Xiao, Lihua; Zhu, Wenwen (Frontiers in Oncology, 2025)
IntroductionDiffuse large B-cell lymphoma (DLBCL) is an aggressive subtype of non-Hodgkin’s lymphoma that predominantly affects the elderly and carries a poor prognosis. When arising in the orbit, DLBCL is characterized by rapid growth, high invasiveness, and a risk of severe vision loss. Despite the use of the R-CHOP regimen, long-term survival outcomes remain suboptimal, highlighting the need for new prognostic biomarkers and therapeutic targets.MethodsWe explored stomatin as a potential prognostic biomarker and therapeutic target for orbital DLBCL. Stomatin expression was analyzed using the GEO database (GSE83632), and Mendelian randomization (MR) analysis was conducted to assess its causal relationship with DLBCL. Immunohistochemistry (IHC) was performed on orbital DLBCL specimens to evaluate stomatin expression. The functional role of stomatin was examined through siRNA-mediated knockdown in DLBCL cell lines, followed by validation using quantitative RT-PCR and Western blot. Cell proliferation, invasion, migration, and apoptosis were assessed using CCK-8, Transwell assays, and flow cytometry.ResultsDatabase analysis revealed elevated stomatin expression in DLBCL, and MR analysis suggested a positive causal association with disease development. IHC confirmed significantly increased stomatin expression in orbital DLBCL tissues, which was associated with poor prognosis based on survival analysis. Vitro assays demonstrated that stomatin knockdown significantly inhibited cell proliferation, migration, and invasion while promoting apoptosis.DiscussionOur findings indicate that stomatin contributes to orbital DLBCL progression and is associated with adverse clinical outcomes. Stomatin may serve as both a prognostic biomarker and a potential therapeutic target for this malignancy.